2017
DOI: 10.7717/peerj.3575
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four prognostic LncRNAs for survival prediction of patients with hepatocellular carcinoma

Abstract: BackgroundAs the fifth most common cancer worldwide, Hepatocellular carcinoma (HCC) is also the third most common cause of cancer-related death in China. Several lncRNAs have been demonstrated to be associated with occurrence and prognosis of HCC. However, identification of prognostic lncRNA signature for HCC with expression profiling data has not been conducted yet.MethodsWith the reuse of public available TCGA data, expression profiles of lncRNA for 371 patients with HCC were obtained and analyzed to find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 35 publications
4
75
0
Order By: Relevance
“…BLCA patients were then categorized into low-and high-risk groups based on the median of the newly calculated prognostic risk score [28,29,31,32]. The whole process is presented in Fig.…”
Section: Construction Of a Prognostic Risk Score With Delsmentioning
confidence: 99%
“…BLCA patients were then categorized into low-and high-risk groups based on the median of the newly calculated prognostic risk score [28,29,31,32]. The whole process is presented in Fig.…”
Section: Construction Of a Prognostic Risk Score With Delsmentioning
confidence: 99%
“…Wang et al 31 also identified a four-lncRNA signature (RP11-322E11.5, RP11-150O12.3, AC093609.1, CTC-297N7.9) which might be an independent prognostic biomarker for the prediction of HCC patient survival. However, compared with previous study, we used more stringent screening criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although TCGA database was previously used to analyze lncRNA-related signatures for HCC prognosis, the present study was different in that it investigated the optimum combination of these prognostic lncRNAs using the ''step'' function in the R platform [46]. Therefore, the prognostic signature constructed in the present study is more accurate than that identified in a previous study [46]. In addition, comprehensive survival analysis of the present 13-DEL prognostic signature was performed by developing a nomogram, and stratified and joint effects survival analysis was performed to investigate its potential application.…”
Section: Discussionmentioning
confidence: 99%
“…He et al, Tang et al and Zang et al used TCGA lncRNA dataset to identify a lncRNA expression-based prognostic signature for assessing the survival of patients with soft-tissue sarcoma, lung cancer, and colorectal adenocarcinoma [36][37][38]. TCGA lncRNA datasets of cutaneous melanoma [39], bladder urothelial carcinoma [40], breast cancer [41], clear cell renal cell carcinoma [42], gastric cancer [43,44], head and neck squamous cell carcinoma [45], and HCC [46] have been used in lncRNA expressionbased prognostic signature investigations by other researchers. These studies used a genome-wide screening method to identify potential prognostic lncRNAs and calculated a risk score based on lncRNA expression.…”
Section: Discussionmentioning
confidence: 99%